The Measurement Model of Professional Operation of State Administration - Milan Rman; Marjan Brezovšek; Janez Stare (Central European Public Administration Review)
This paper presents the study of a measurement model of professional operation of state administration. From the perspective of reliable performance of state functions, the professional operation of state administration represents one of the goals of social change. Based on theoretical-analytical findings, a measurement model of professional operation of state administration was designed. It consists of three dimensions, namely: reliability of state administration, professionalisation of the administrative profession, and competence of employees. The reliability dimension is represented by the element of legality and economic efficiency, the profession dimension is based on power, autonomy, knowledge and responsibility, and the competence dimension includes elements of leadership and ethics. The measurement model was tested in the Slovenian state administration. The results of the research confirm the connection between the three aforementioned dimensions of professional operation of state administration and, consequently, the validity of the designed model.